2005
DOI: 10.1063/1.1869543
|View full text |Cite
|
Sign up to set email alerts
|

A continuum model for zigzag single-walled carbon nanotubes

Abstract: An idea of “spatial periodic strain” is proposed and an equilibrium relationship is established for the mechanics of zigzag single-walled carbon nanotubes (SWCNTs). An efficient approach is presented to investigate mechanical properties of zigzag SWCNT, and its validity is demonstrated by comparing its calculation results with existing results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The closed-form expressions for elastic properties of achiral SWCNTs under various loading conditions were presented by Shen and Li 64 via a energy approach. Leung et al 65 obtained Young's modulus for zigzag CNTs by developing an equivalent truss model. These expressions are concise but capable of directly linking material properties at different length scales.…”
Section: Introductionmentioning
confidence: 99%
“…The closed-form expressions for elastic properties of achiral SWCNTs under various loading conditions were presented by Shen and Li 64 via a energy approach. Leung et al 65 obtained Young's modulus for zigzag CNTs by developing an equivalent truss model. These expressions are concise but capable of directly linking material properties at different length scales.…”
Section: Introductionmentioning
confidence: 99%
“…From Table 1, compared with the stiffness parameters given by Li and Chou (2003), Leung et al (2005) and Odegard et al (2002), it can be observed that the stretch stiffness and bending stiffness of beam element are reduced but the torsion stiffness is unchanged. Two truss elements are added to compensating the reduced stiffness.…”
Section: Inter-belt Modelmentioning
confidence: 88%
“…Different kinds of structural models have been developed in the past years, such as the beam model given by Li and Chou (2003) (see Fig. 2), the rod model suggested by Odegard et al (2002), and another rod model given by Leung et al (2005) (see Fig. 3).…”
Section: Structural Mechanics Models Of Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Their extraordinary strength, unique electrical properties and their ability to conduct heat efficiently have generated considerable interest among both experimentalists and theoreticians. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Nanotubes may also be produced by synthesis methods, for instance multi-wall nanotubes (MWNTs) which consist of multiple layers of graphene rolled in on themselves to form a cylindrical tube. There are two models which can be used to describe the structures of multi-wall nanotubes.…”
Section: Introductionmentioning
confidence: 99%